Land Redistribution in Limpopo Province: A Case of Greater Letaba Municipality - Malahlela, T. (International Conference on Public Administration and Development Alternative (IPADA), 2019)
The aim of this paper is to show the challenges that the land redistribution programme in Limpopo Province is faced with. Furthermore, the paper tries to show whether the policy of land redistribution can be effective or not. In addition, it will be established whether the land redistribution might benefit the Previously Disadvantaged Individuals (PDIs) as the department's mandate. Blacks were dispossessed of land which disadvantaged them to access land for residential and agriculture. The paper used the qualitative approach with primary and secondary data together with literature. The data for this paper was collected through questionnaires and interviews. The sample for this paper was collected from land beneficiaries of Greater Letaba Municipal area, members of traditional councils, members of municipal council and government department officials for both Department of Agriculture and Department of Rural Development and Land Reform in the area. The paper revealed the need for coordination amongst the state departments to ensure maximum support of the land redistribution beneficiaries. The Department of Agriculture should support the Department of Rural Development and Land Reform with extension services. The paper concludes that the level of organisation within the land redistribution projects needed to be improved with some constantly experience conflicts amongst beneficiaries. This reflects the lack of organisational skills amongst project beneficiaries
Article published in the 4th Annual International Conference on Public Administration and Development Alternatives 03 - 05 July 2019, Southern Sun Hotel, OR Tambo International Airport, Johannesburg, South Africa
Keywords: Historical imbalances; Land redistribution; Land reform; Land dispossession; Landless; Previously disadvantaged communities; Land reform--South Africa; Land reform beneficiaries--South Africa